2023
DOI: 10.1021/acs.est.2c05583
|View full text |Cite
|
Sign up to set email alerts
|

Snow-Dependent Biogeochemical Cycling of Polycyclic Aromatic Hydrocarbons at Coastal Antarctica

Abstract: The temporal trend of polycyclic aromatic hydrocarbons (PAHs) in coastal waters with highly dynamic sources and sinks is largely unknown, especially for polar regions. Here, we show the concurrent measurements of 73 individual PAHs and environmental data, including the composition of the bacterial community, during three austral summers at coastal Livingston (2015 and 2018) and Deception ( 2017) islands (Antarctica). The Livingston 2015 campaign was characterized by a larger snow melting input of PAHs and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In the Pearl River Estuary, a hydrological model has revealed that the discharge of erythromycin-H 2 O and sulfamethoxazole through outlets accounts for 30.8 and 6.74% of their environmental capacity, respectively . Humans can be exposed to antibiotics through seafood consumption, thus prompting the need for systemic investigation of bioaccumulation, hazard evaluation, and risk assessments in aquatic organisms. Once in the water column, the biological pump and degradation largely determine the fate of organic pollutants. , Previous studies have demonstrated that the phytoplankton biological pump plays an important role in regulation of water column mass balance and burial of antibiotics in eutrophic ecosystems, which could further affect the fate and trophic transfer behaviors of antibiotics in food webs. , Consistently higher bioaccumulation factors (BAFs) of other organic pollutants, such as perfluorooctanoate (PFOA), in oceanic plankton have been found in large oligotrophic global oceans . A recent work indicated that the effects of the biological pump further enhanced the uptake of sediment-bound hydrophobic organic contaminants (HOCs) by benthos and phytoplankton could strengthen the benthic bioaccumulation of HOCs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Pearl River Estuary, a hydrological model has revealed that the discharge of erythromycin-H 2 O and sulfamethoxazole through outlets accounts for 30.8 and 6.74% of their environmental capacity, respectively . Humans can be exposed to antibiotics through seafood consumption, thus prompting the need for systemic investigation of bioaccumulation, hazard evaluation, and risk assessments in aquatic organisms. Once in the water column, the biological pump and degradation largely determine the fate of organic pollutants. , Previous studies have demonstrated that the phytoplankton biological pump plays an important role in regulation of water column mass balance and burial of antibiotics in eutrophic ecosystems, which could further affect the fate and trophic transfer behaviors of antibiotics in food webs. , Consistently higher bioaccumulation factors (BAFs) of other organic pollutants, such as perfluorooctanoate (PFOA), in oceanic plankton have been found in large oligotrophic global oceans . A recent work indicated that the effects of the biological pump further enhanced the uptake of sediment-bound hydrophobic organic contaminants (HOCs) by benthos and phytoplankton could strengthen the benthic bioaccumulation of HOCs …”
Section: Introductionmentioning
confidence: 99%
“…6−9 Once in the water column, the biological pump and degradation largely determine the fate of organic pollutants. 10,11 Previous studies have demonstrated that the phytoplankton biological pump plays an important role in regulation of water column mass balance and burial of antibiotics in eutrophic ecosystems, which could further affect the fate and trophic transfer behaviors of antibiotics in food webs. 12,13 Consistently higher bioaccumulation factors (BAFs) of other organic pollutants, such as perfluorooctanoate (PFOA), in oceanic plankton have been found in large oligotrophic global oceans.…”
Section: ■ Introductionmentioning
confidence: 99%